A MAGNIFIED BEAM ALGORITHM TO DETERMINE THE COUPLING RATIOS OF R/C COUPLED SHEAR WALL - Doran, Bilge (JOHN WILEY & SONS LTD, 2009)
The structural behaviour of a coupled shear wall (CSW) is greatly affected by the geometrical and mechanical properties of the coupling beams. The coupling ratio (r) is defined to represent the proportion of overturning moment resisted by each individual shear wall. The coupling ratio (r) is considered to be a key parameter in the nonlinear analysis and design of CSWs. In this study, the coupling ratios are determined on the basis of magnified beam analysis, using a statistical approach. An adequate number of CSWs have been selected with varying geometrical and mechanical properties, and the coupling ratios have been determined for each case using a magnified beam algorithm. The structural analyses have been also performed by the finite element modelling, and relationships for the estimation of the coupling ratios are provided using nonlinear regression analyses. The magnified beam approach adapted in this study is therefore proven to be capable of providing accurate and practical estimates for the coupling ratios of R/C CSWs. The results are quite promising for further research of any expanded data sets. Copyright (C) 2009 John Wiley & Sons. Ltd.
Keywords: Construction & Building Technology; Engineering